Analysis of Tensile and Bend Strength with Current and Voltage Variations in GMAW Welded Joints of SS400 Steel for Train Underframes - Muhammad Fahrurozy Pradaya; Heri Wibowo (Journal of Applied Mechanical Engineering Innovation, 2026)
This study investigates the effect of welding current and voltage variations on the tensile and bend strength of Gas Metal Arc Welding (GMAW) joints in SS400 steel for train underframe applications. SS400 steel plates with a thickness of 4.5 mm were welded using a single-V groove with a 60° angle. The welding parameters consisted of two current levels, 100 A and 120 A, and three voltage levels, 20 V, 23 V, and 26 V. The research used a quantitative experimental method. The tensile test data were analyzed by calculating the average maximum tensile strength and elongation, while the bend test results were evaluated based on visual defects on the convex surface of the specimens. The results show that the 100 A-23 V parameter produced the highest average maximum tensile strength of approximately 458.3 MPa with an average elongation of 13.9%. However, the bend test results indicated that the safest and most acceptable parameter was 120 A with moderate voltage, particularly 23 V, because the specimens showed no visible defects after testing. Therefore, the 120 A-23 V welding parameter is considered the most optimal combination for balancing tensile strength and bend toughness in GMAW welded joints of SS400 steel for train underframe structures